Financial Performance Analysis Using Economic Value Added and Market Value Added Methods - Ariefah SUNDARI; Ahmad Fathur ROZI; Ana Fitriyatul BILGIES; Ali MUHAJIR (PT Keberlanjutan Strategis Indonesia, 2023)
This study aims to determine and analyze financial performance with the Economic Value Added and Market Value Added methods in the Cement Sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The research method used is a quantitative method with a descriptive approach and the sampling technique in this study is a purposive sampling technique. The data collection techniques used used secondary data through library studies and documentation studies obtained through the website https://www.idx.co.id in the form of a Balance Sheet and Profit and Loss Report for the Year 2017-2021. The results of this study are that the three cement companies have a positive EVA value which means they have succeeded in creating economic value, and one company has a negative EVA value at PT Semen Baturaja Tbk which means the company is not able to provide added value in 2021. means providing added value through market capitalization value.